2015
DOI: 10.1530/joe-15-0316
|View full text |Cite
|
Sign up to set email alerts
|

Odontella aurita-enriched diet prevents high fat diet-induced liver insulin resistance

Abstract: The beneficial effect of polyunsaturated omega-3 fatty acid (w-3 FA) consumption regarding cardiovascular diseases, insulin resistance and inflammation has been widely reported. Fish oil is considered as the main source of commercialized w-3 FAs, and other alternative sources have been reported such as linseed or microalgae. However, despite numerous reports, the underlying mechanisms of action of w-3 FAs on insulin resistance are still not clearly established, especially those from microalgae. Here, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, IL-4 and IL-10 levels were increased in the plasma and adipose tissue of the HF-Phaeo group, reflecting the partial restoration of the basal inflammatory status in rats supplemented with P. tricornutum . Thus, P. tricornutum could play a preventive role against inflammation and insulinoresistance, as observed in a previous study that used the EPA-rich microalga O. aurita as a food supplement in the HF diet [68]. The restoration of inflammatory status and insulinemia could be due to various molecules contained in P. tricornutum such as the carotenoid pigments, which are known anti-inflammatory agents [69].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, IL-4 and IL-10 levels were increased in the plasma and adipose tissue of the HF-Phaeo group, reflecting the partial restoration of the basal inflammatory status in rats supplemented with P. tricornutum . Thus, P. tricornutum could play a preventive role against inflammation and insulinoresistance, as observed in a previous study that used the EPA-rich microalga O. aurita as a food supplement in the HF diet [68]. The restoration of inflammatory status and insulinemia could be due to various molecules contained in P. tricornutum such as the carotenoid pigments, which are known anti-inflammatory agents [69].…”
Section: Discussionmentioning
confidence: 80%
“…Flaxseed oil effectively normalized the activity of JNK signaling, which was accompanied by the restored ER homeostasis and improved insulin signaling in mice liver. However, Amine et al had found that EPA/DHA alleviated HFD-induced insulin resistance through inhibiting the phosphorylation of JNK . Therefore, we speculated that n-3PUFA-mediated modulation of JNK signaling might depend on the metabolic context.…”
Section: Discussionmentioning
confidence: 90%
“…However, Amine et al had found that EPA/DHA alleviated HFD-induced insulin resistance through inhibiting the phosphorylation of JNK. 51 Therefore, we speculated that n-3PUFA-mediated modulation of JNK signaling might depend on the metabolic context.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our study provides evidence that PT is a valuable source for EPA, as described before for another diatom, Odontella aurita, which has been already authorized as whole algae, although no nutritional human trials are available so far, in which Odontella aurita has been tested for safety or bioavailability of its ingredients. The nutritional composition of Odontella aurita is quite similar to that of PT [37] and the microalgae have been shown in pre-clinical studies to reduce risk factors for metabolic syndrome [38,39] similar to PT [23]. Although Odontella aurita has been approved as whole microalgae, only 0.5-1.5% of it is allowed in food, mainly for flavoring [22].…”
Section: Discussionmentioning
confidence: 99%